Fenomena Gated Community di Perkotaan - Lestiyono, Sidik (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The phenomenon of gated communities in urban areas reflects transformations in settlement patterns, security and social dynamics of modern society. Gated communities, which are surrounded by fences or walls with limited access, have become an option for some urban communities to create a safer, exclusive and controlled environment. This research explores the impact of this phenomenon on security, economic polarization, social isolation, exclusive facilities, and city identity. The results highlight the challenges and opportunities associated with the development of gated communities, and emphasize the need for an integrated approach to creating inclusive and sustainable settlements in modern cities.